2006
DOI: 10.3748/wjg.v12.i48.7874
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic ganglioneuromatosis of esophagogastric junction in a patient with gastro-esophageal reflux disorder and intestinal metaplasia

Abstract: A 58-year-old female with a recurrent history of upper abdominal pain and intermittent dysphagia underwent endoscopic evaluation that demonstrated an irregular and nodular esophago-gastric (EG) junction and grade I erosive esophagitis. Biopsies showed prominent intestinal metaplasia of Barrett's type without dysplasia, chronic inflammation and multiple aggregates of large cells within the mucosal lamina propria, some with spindle shaped nuclei. Immunohistochemistry stains for keratins AE-1/AE-3 were negative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…2 Case report by Al-Rikabi AC et al described case presented with gastic outlet obstruction 6 similar to our case study whereas case study done by Siderits R et al, described reflex esophagitis as the presenting feature. 7 Gastric muscular mural hypertrophy and hyperplasia of nerve fibers may lead to stricture causing gastric outlet obstruction, as Al-Rikabi AC et al, found in their case described severe gastric outlet obstruction, most probably caused by a combination of muscular mural hypertrophy and hyperplasia of the myenteric plexus leading to stricture formation, 6 similar morphology seen in the present case study as well.…”
Section: Discussionsupporting
confidence: 82%
“…2 Case report by Al-Rikabi AC et al described case presented with gastic outlet obstruction 6 similar to our case study whereas case study done by Siderits R et al, described reflex esophagitis as the presenting feature. 7 Gastric muscular mural hypertrophy and hyperplasia of nerve fibers may lead to stricture causing gastric outlet obstruction, as Al-Rikabi AC et al, found in their case described severe gastric outlet obstruction, most probably caused by a combination of muscular mural hypertrophy and hyperplasia of the myenteric plexus leading to stricture formation, 6 similar morphology seen in the present case study as well.…”
Section: Discussionsupporting
confidence: 82%
“…Patients with polypoid ganglioneuroma are not associated with NF1, MEN2b or other genetic syndromes. [10] The second type, ganglioneuromatous polyposis is characterized by numerous (more than 20) mucosal and/or submucosal polyps with a sessile or pedunculated form, and is predominately located in the colon and terminal ileum. [11] Ganglioneuromatous polyposis can be isolated or associated with one of the following syndromes: MEN2b, NF1, Cowden disease, non-familial colic polyposis or juvenile polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…The differing clinical symptoms found in neurofibromatosis of the hindgut tract depend on the lesion characteristics, such as the location, motility, and adjacent structures of the affected tract. Clinical presentation of the lesions can be abdominal pain[ 4 ], gut obstruction[ 6 , 7 ], palpable masses[ 8 ], constipation[ 9 ], or diarrhea[ 10 ].…”
Section: Discussionmentioning
confidence: 99%